2004
DOI: 10.2214/ajr.183.2.1830315
|View full text |Cite
|
Sign up to set email alerts
|

Size and Morphology of the Trachea Before and After Lung Volume Reduction Surgery

Abstract: Our data suggest that tracheal dimensions reflect the severity of emphysema as reflected by increased lung volumes. Tracheal features were poor predictors of changes in postsurgical pulmonary function parameters evaluated in this preliminary study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…The observed strong negative correlations for the normalized trachea length suggest the effect of the trachea on air transport and thereby, indirectly, gas exchange. Our limited observation in this regard is in agreement with Leader et al (15) and extends in part the more extensive investigation to a larger and more diverse data set. Airway resistance (eg, lung resistance at 5 Hz and lung resistance at 20 Hz) decreases and airway reactance (ie, lung reactance at 5 Hz) increases with larger airway architecture because resistance depends on the number of parallel pathways present.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The observed strong negative correlations for the normalized trachea length suggest the effect of the trachea on air transport and thereby, indirectly, gas exchange. Our limited observation in this regard is in agreement with Leader et al (15) and extends in part the more extensive investigation to a larger and more diverse data set. Airway resistance (eg, lung resistance at 5 Hz and lung resistance at 20 Hz) decreases and airway reactance (ie, lung reactance at 5 Hz) increases with larger airway architecture because resistance depends on the number of parallel pathways present.…”
Section: Discussionsupporting
confidence: 93%
“…McDonough et al (13) and Diaz et al (14) studied the relationship between manually ascertained airway branch counts and the severity of emphysema and found that total airway count was lower in subjects with emphysema, suggesting that the number of airway branches may be associated with lung function. Leader et al (15) reported that tracheal features changed significantly from before to after lung volume reduction surgery and concluded that combining PFT and tracheal imaging features could potentially provide a more accurate assessment of disease status and progression. Handa et al (16) verified this observation, reporting a positive correlation between tracheal area corrected for body surface area and percentage peak expiratory flow and a negative correlation between wall area percentage and percentage peak expiratory flow.…”
mentioning
confidence: 99%
“…Griscom and Wohl found that the similarity in tracheal lengths between male and female subjects persists into the teenage years 33 . The difference in tracheal length between genders appears to be at least somewhat attributable to post-pubescent changes 17,22,23,[32][33][34] . Based on the studies available, it is unclear if race, as an independent variable, affects tracheal length.…”
Section: Static Patient Factors: Race and Gender (Table 1)mentioning
confidence: 99%
“…It is intuitively obvious that over wide ranges of height in patients, tracheal length correlates with patient height. This is abundantly clear in the paediatric population where wide ranges in patient height exist 17,21,[30][31][32][33][34] . In the adult population, the ranges in height are not as dramatic and the correlation between patient stature and tracheal length reported in studies is not as strong, but does exist 22,23,[25][26][27]37 .…”
Section: Static Patient Factor: Heightmentioning
confidence: 99%
“…Next, we started estimating trachea volume from the first axial slice that we found the trachea region with the Hough transform. Expected maximum capacity of trachea (i.e., < 30 cm 3 ) [52] and the rate of change of the volume were used to determine the stopping criteria for trachea inclusion/exclusion in the final segmentation. Note that main bronchi were not removed due to the capacity constraint feature of the trachea removal tool.…”
Section: Methodsmentioning
confidence: 99%